Educational Renewal During Muhammad Ali Period and Its Impact on The Al-Azhar Educational Institution - Hasneli, Hasneli; Meirison, Meirison; Muhammadi, Qasem (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This article describes Muhammad Ali's educational endeavors since he came to power in 1805. Muhammad Ali built schools and brought in European teachers to teach, and he aimed to take advantage of scientific developments in European countries to create a modern Egypt. By conducting a literature study and a qualitative approach, we analyze the sources obtained and describe them historically using a qualitative approach. Muhammad Ali had strong ambitions to become the sole ruler of the Middle East and his descendants. For this reason, a strong army is needed for this ambition. A strong military cannot come without medicine, chemistry, physics, civil engineering, and language education. His efforts succeeded brilliantly after experiencing obstacles almost on par with all European countries. However, this effort is detrimental to Islamic Education and Al-Azhar by building schools that sometimes do not follow Islamic teachings and rule out Arabic as the language of the Koran. Even so, public Education did not continue and run as it should because Western countries stopped Muhammad Ali's ambition to build a modern state. After all, the interests of the West and Russia were disrupted.